Peningkatan Kapasitas Pelaku Usaha Homestay Desa Wisata di Kabupaten Biak Numfor, Provinsi Papua - Fitriana, Rina (Jurnal Pemberdayaan Pariwisata, 2020)
Biak Numfor was a success story in tourism during 90s by becoming one of transit areas for aircraft going to Los Angeles, USA. One of the evidences was the existence of the first 5 star hotels in Papua, namely Merauw Hotel, which was destroyed during 1998 riot.  The main problems faced by the Government in this area are the conflict about indigenous land and the human resources problems in tourism, including the lack of knowledge and skills of business actors in tourist village. With the goal of increasing the capacity of homestay business owners in operating its business unit, the Ministry of Tourism that becomes a partner in this community service holds the homestay training for 70 homestay owners who come from several tourist villages. The training held for one day at Mapia Hotel, Biak Numfor District, Papua Province on October 16, 2019. The result of this community service is the increasing knowledge of the homestay owners on the basic knowledge of homestay operations as much as 60%. In addition, 100% of the participants stated such training as something very enlightening and increasing their understanding and expertise in homestay.